Environmental remediation of dye effluents using Gracilaria edulis (Marine red alga) mediated green synthesized Ag₂O nanoparticles: Impacts on soil and water quality - G. Visu; N. Muruganantham; P. Anitha; R. Govindharaju; V. Anusuya (Environmental Nanotechnology, Monitoring & Management, 2026)

Marker-based standardisation and in-vitro biological activity evaluation of Sudarshanam tablet – an important ayurvedic formulation - Veena K Namboodiri; Tom Cherian; Anitha R; Swathi M; Suresh V Nampoothiri (Natural Product Research, 2026)

Pollen micromorphology and functional traits as indicators of genetic diversity in Elaeis spp. - M. Neema; S. Suresh; G. Somasundaram; S. G. Silpa; R. P. Premalatha; P. Anitha; G. M. Aswathy (Genetic Resources and Crop Evolution, 2026)

Metformin for knee osteoarthritis in overweight and obese adults: a systematic review and meta-analysis of efficacy, safety, and disease-modifying anti-inflammatory potential - Santenna Chenchula; Krishna Chaitanya Amerneni; R. Padmavathi; K. Anitha; Mohan Krishna Ghanta; Shriraam Karunakaran; Shubham Atal; Sunil Kumar; Pavani Saggurthi; Shoibam Jenifa; K. Mythili Bai; Madhavrao Chavan; et al. (Inflammopharmacology, 2026)

Ingenious design and application of ZnAl-LDH/BiOBr Z-scheme heterojunction for effective photocatalytic degradation of tetracycline in aqueous environment: Insight into mechanism and toxicity estimation - R. Janani; M. Kanagalakshmi; S. Gopika Devi; Anitha Pius (Process Safety and Environmental Protection, 2026)

Smoke-derived microplastics of polypropylene In Vitro proliferative impact on human lung adenocarcinoma cells: Physicochemical analysis and biological evaluation - Nivedita Jha; Angshita Das; Megha Prasanth; S. Daisy Precilla; R. Sivachandran; Rajaneesh Anupam; T.S. Anitha (Environmental Toxicology and Pharmacology, 2026)

Photocatalytic hydrogel impregnated CoMgAl layered double oxide and biochar for visible light driven degradation of agrochemical contaminants in real water matrices - M. Kanagalakshmi; Nanthan kumar T.R.; R. Janani; Anitha Pius (Chemical Engineering Journal, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

One step facile green synthesis of ZnFe2O4-ZnO Nanocomposite: Efficient photocatalytic activity towards organic dyes under visible light and photoluminescence applications - E.Vinay Kumar; R. Harini; Anitha; B.E. Kumara Swamy; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2025)

A Spectroscopic Investigation into the Stability of Carbon Dots Derived from Polyethylene Glycol - K. R. Athulya; Arathy Chandran; Tirupati Rao Bantu; Anitha C. Kumar (Journal of Fluorescence, 2025)

Recent Insights into the Neurobiology of Alzheimer’s Disease and Advanced Treatment Strategies - Anitha K; Mandeep Kumar Singh; Komal Kohat; Sri Varshini T; Santenna Chenchula; Padmavathi R; Lakshmi Sahitya Amerneni; Vishnu Vardhan K; Mythili Bai K; Madhav Rao Chavan; Shvetank Bhatt (Molecular Neurobiology, 2025)

Spectroscopic Investigation of Hydrogels Formed from Phenylalanine - Arathy Chandran; K. R. Athulya; Anitha C. Kumar (Journal of Fluorescence, 2024)

Cymodocea serrulata as sources of biopesticides: A novel approach managing crop insects in Solanum melongena L. (Solanales: Solanaceae) - Mythili Ravichandran; Rani Elavarasan Anitha; B.T. Sureshkumar; T.T. Ajith Kumar; Salim Manoharadas; Naushad Ahmad; Mohammad Rizwan Khan; R. Dineshkumar (Sustainable Chemistry and Pharmacy, 2024)

Exploring the potential therapeutic benefits of 7-methoxy coumarin for neuropathy pain: an in vivo, in vitro, and in silico approach - Binoy Varghese Cheriyan; Jaikumar Shanmugasundaram; Prakash Ramakrishnan; Kavitha Ramasamy; R. Karthikeyan; Sowmyalakshmi Venkataraman; Anitha Roy; Parameswari Royapuram Parthasarathy (Molecular Biology Reports, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Identification of sources of resistance and comparative metabolomic profiling of resistant and susceptible chilli germplasm to Meloidogyne incognita Race 1 - Prasanna Holajjer; T. P. Ahammed Shabeer; M. K. Mahatma; Z. Khan; S. R. Pandravada; N. Sivaraj; Anitha Kodaru; Anita Pardeshi (Australasian Plant Pathology, 2024)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Dissipation and evaluation of different treatments on the residues of different insecticides in/on cauliflower curd - Anitha Vijay; Ravi L. Kalasariya; Paresh H. Rathod; Suchi Chawla; Rajesh R. Acharya (Food Additives & Contaminants: Part A, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Silicon nanoparticles (SiNPs): Challenges and perspectives for sustainable agriculture - M. Yuvaraj; R. Sathya Priya; N. Jagathjothi; M. Saranya; N. Suganthi; R. Sharmila; Jaiby Cyriac; R. Anitha; K.S. Subramanian (Physiological and Molecular Plant Pathology, 2023)

A Simplified Isothermal Recombinase Polymerase Amplification Assay for Detection of Sugarcane bacilliform virus Infection - B. Parameswari; S. K. Sharma; L. Karthikaiselvi; Baby Wangkhem; K. Nithya; R. Viswanathan; G. P. Rao; V. Celia Chalam; K. Anitha (Sugar Tech, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

Assessment of diversity in anti-nutrient profile, resistant starch, minerals and carbohydrate components in different ricebean (Vigna umbellata) accessions - Paras Sharma; Giridhar Goudar; Anil Kumar Chandragiri; R. Ananthan; K. Subhash; Anitha Chauhan; T. Longvah; Mohar Singh; Rakesh Bhardwaj; Swarup Kumar Parida; Amit Kumar Singh; Gayacharan; et al. (Food Chemistry, 2023)

Coupled physical-biogeochemical simulations of upwelling, ecological response to fresh water - Anitha Gera; R Gayathri; P Ezhilarasan; V Ranga Rao; M V Ramana Murthy (Ecological Modelling, 2023)

Effect of coinfections on neurocognitive functioning among people with clade C HIV infection in Zambia - Lumbuka Kaunda; Mary S. Ngoma; J. Anitha Menon; Robert K. Heaton; Sara Gianella; Ajay R. Bharti; Scott Letendre; Michelli Faria de Oliveira; Knut A. Hestad (Journal of NeuroVirology, 2023)

Biogenic synthesis of copper nanoparticles using Vitis vinifera L. seed extract, and its in-vitro biological applications - Janakiraman Vardhana; Ramarajan Sivasankaran; Thakku R. Ramkumar; Jeyachandran Anitha (Journal of Plant Biochemistry and Biotechnology, 2022)

Influence of salinity on the meiofaunal distribution in a hypersaline lake along the southeast coast of India - Pandiya rajan R S; Anitha Gera; Ramu K; Ranga Rao V; Ramanamurthy MV (Environmental Monitoring and Assessment, 2022)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

Genetic and genomic resources, and breeding for accelerating improvement of small millets: current status and future interventions - M. Vetriventhan; Vania C. R. Azevedo; H. D. Upadhyaya; A. Nirmalakumari; Joanna Kane-Potaka; S. Anitha; S. Antony Ceasar; M. Muthamilarasan; B. Venkatesh Bhat; K. Hariprasanna; Amasiddha Bellundagi; Deepika Cheruku; et al. (The Nucleus, 2020)
Current agricultural and food systems encourage research and development on major crops, neglecting regionally important minor crops. Small millets include a group of small- seeded cereal crops of the grass family Poaceae . This includes finger millet, foxtail millet, proso millet, barnyard millet, kodo millet, little millet, teff, fonio, job’s tears, guinea millet, and browntop millet. Small millets are an excellent choice to supplement major staple foods for crop and dietary diversity because of their diverse adaptation on marginal lands, less water requirement, lesser susceptibility to stresses, and nutritional superiority compared to major cereal staples. Growing interest among consumers about healthy diets together with climate-resilient features of small millets underline the necessity of directing more research and development towards these crops. Except for finger millet and foxtail millet, and to some extent proso millet and teff, other small millets have received minimal research attention in terms of development of genetic and genomic resources and breeding for yield enhancement. Considerable breeding efforts were made in finger millet and foxtail millet in India and China, respectively, proso millet in the United States of America, and teff in Ethiopia. So far, five genomes, namely foxtail millet, finger millet, proso millet, teff, and Japanese barnyard millet, have been sequenced, and genome of foxtail millet is the smallest (423-510 Mb) while the largest one is finger millet (1.5 Gb). Recent advances in phenotyping and genomics technologies, together with available germplasm diversity, could be utilized in small millets improvement. This review provides a comprehensive insight into the importance of small millets, the global status of their germplasm, diversity, promising germplasm resources, and breeding approaches (conventional and genomic approaches) to accelerate climate-resilient and nutrient-dense small millets for sustainable agriculture, environment, and healthy food systems.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Tuta absoluta continues to disperse in Asia: damage, ongoing management and future challenges - Peng Han; Yunus Bayram; Liora Shaltiel-Harpaz; Fariba Sohrabi; Anitha Saji; Uulu Tair Esenali; Anvar Jalilov; Abid Ali; Pathour R. Shashank; Khasan Ismoilov; Zhao-zhi Lu; Su Wang; et al. (Journal of Pest Science, 2019)

Evaluation of Circulating Plasma VEGF-A, ET-1 and Magnesium Levels as the Predictive Markers for Proliferative Diabetic Retinopathy - Gopal Niranjan; A. R. Srinivasan; K. Srikanth; Gowda Pruthu; R. Reeta; Ramasamy Ramesh; Rajendiran Anitha; V. Mohana Valli (Indian Journal of Clinical Biochemistry, 2019)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

Molecular characterization of Indian isolate of peanut mottle virus and immunodiagnosis using bacterial expressed core capsid protein - K. Soumya; M. Yogita; Y. Prasanthi; K. Anitha; P. B. Kavi Kishor; R. K. Jain; Bikash Mandal (VirusDisease, 2014)

MARSpline model for lead seven-day maximum and minimum air temperature prediction in Chennai, India - K Ramesh; R Anitha (Journal of Earth System Science, 2014)

Coregulation of host–response genes in integument: switchover of gene expression correlation pattern and impaired immune responses induced by dipteran parasite infection in the silkworm, Bombyx mori - Anitha Jayaram; Appukuttan Nair R. Pradeep; Arvind K. Awasthi; Geetha N. Murthy; Kangayam M. Ponnuvel; Sirigineedi Sasibhushan; Guruprasad C. Rao (Journal of Applied Genetics, 2014)

Plantlet regeneration through indirect shoot organogenesis and somatic embryogenesis in Justicia gendarussa Burm. f., a medicinal plant - N. Bhagya; K. R. Chandrashekar; Anitha Karun; U. Bhavyashree (Journal of Plant Biochemistry and Biotechnology, 2013)

Antihypercholesterolemic and antioxidative effects of an extract of the oyster mushroom, Pleurotus ostreatus, and its major constituent, chrysin, in Triton WR-1339-induced hypercholesterolemic rats - Ramalingam Anandhi; Thangaraj Annadurai; Thirugnanasambandhar S. Anitha; Arumugam R. Muralidharan; Kalifulla Najmunnisha; Vasanthi Nachiappan; Philip A. Thomas; Pitchairaj Geraldine (Journal of Physiology and Biochemistry, 2013)

Activation of autophagic programmed cell death and innate immune gene expression reveals immuno-competence of integumental epithelium in Bombyx mori infected by a dipteran parasitoid - Appukuttan Nair R. Pradeep; Jayaram Anitha; Arvind K. Awasthi; Mohd. A. Babu; Murthy N. Geetha; Hariharan K. Arun; Sagar Chandrashekhar; Guruprasad C. Rao; Nanjappa B. Vijayaprakash (Cell and Tissue Research, 2013)

Estimation of atmospheric surface layer parameters and numerical simulation using MM5 at Mangalore, West Coast of India - Anitha Kumari Hegde; R. Venkatesan; C. V. Srinivas; K. M. Balakrishna (Meteorology and Atmospheric Physics, 2010)

Liposome Damage and Modeling of Fragments of Human Islet Amyloid Polypeptide (IAPP) Support a Two-Step Model of Membrane Destruction - Deborah L. Heyl; Joshua M. Osborne; Sarika Pamarthy; Shyamprasad Samisetti; Andrew W. Gray; Anitha Jayaprakash; Srikanth Konda; Dorothy J. Brown; Samuel R. Miller; Reza Eizadkhah; Maria C. Milletti (International Journal of Peptide Research and Therapeutics, 2010)

Application of Isozyme Data in Fingerprinting Napier Grass (Pennisetum purpureum Schum.) for Germplasm Management - Anitha P. Bhandari; D. H. Sukanya; C. R. Ramesh (Genetic Resources and Crop Evolution, 2006)

Glutathione S-transferase M1 and T1 null genotype distribution in South Indians - A.T. Naveen; C. Adithan; N. Padmaja; C.H. Shashindran; B.K. Abraham; K. Satyanarayanamoorthy; P. Anitha; N. Gerard; R. Krishnamoorthy (European Journal of Clinical Pharmacology, 2004)